Effect of Substitution of Kaopi and Anchovy Flour Based on The Nutritional Values, Organoleptic, and Total Microbe of ‘Kasuami/kasoami’ - Mamangkey, Jendri (International Journal of Scientific Research in Biological Sciences, 2022)
These low contents demand necessary to conduct substitution using anchovy flour (Stolephorus comesonii) since it has a quite complete nutritional content, such as fat, protein, and carbohydrates. This research was carried out aiming to discover the effect of substitution between kaopi flour and anchovy flour on the nutritional content of kasuami/kasoami and the appropriate ratio of kaopi flour and anchovy flour proportions for a good kasuami/kasoami products in terms of color, aroma, and taste based on organoleptic tests and microbial growth. This study employed a completely randomized design with 6 treatment levels and 3 replications. The treatment levels were done on the proportion of kaopi flour and anchovy flour (S. comersonii), in which the ratio iwasT0 (100%:0%). T1 (98%:2%). T2 (96%:4%). T3 (94%:6%). T4 (92%:8%). and T5 (90%:10%). The best kasuami/kasoami was obtained from the substitution of kaopi flour using anchovy flour by 90% kaopi: 10% anchovy flour (T5). The results of kasuami/kasoami chemical test based on the best treatment provided indicated that the substitution of kaopi flour using anchovy flour significantly affected the variables of moisture content (47.57%). protein content (16.40%). fat content (3.48%). carbohydrate content (28.86), and total microbes (202.33 x 10-2 cfu). Meanwhile, based on the organoleptic test, the average preference values for color was 4.47 (preferred), the aroma was 5.40 (preferred), and the taste was 6.13 (preferred). This research data indicate that anchovy flour as a substitute for kaopi flour in producing kasuami/kasoami significantly affected the chemical composition variables.